E-4: ANALYSIS OF SOCIAL AND INSTITUTIONAL DETERMINANTS OF TAX REVENUE BUOYANCY IN PAKISTAN - Shahzada, Naseer; Mughal, Khalid Mahmood (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
This study intended to explore the effect of social and institutional variables on tax buoyancy in Pakistan. The study employed the Time Series Data from 1991 to 2021. The analysis was done through Engel Granger type of co-integration and ARDL co-integration. The study revealed that buoyancy (-1), literacy rate, life expectancy, fiscal decentralization, rule of law and political stability have direct impact on the tax buoyancy. While unemployment, urbanization, corruption and Govt, effectiveness have inverse impact on the tax revenue buoyancy. This study advised to eradicate the unemployment and to increase the documentation of economy. This study also advised to enhance elementary and higher education, take measure to improve the rule of law and to create a transparent and accountable legal system. Again it also suggested to avoid political victimization, conduct free and fair election, should make an effective local body system, should work on the Devolution of Power & Responsibility, promote good governance, restructure the tax system, to make the institutional effective and judicious.